Modelo de migración de software propietario a software libre caso de estudio: Universidad Técnica de Cotopaxi. - Charco Timbila, Jefferson Paul (2021)
In this research work, a migration model from proprietary software to free software is proposed at the Technical University of Cotopaxi, to reduce the high cost of licensing computer applications and comply with Decree 1014, which through an executive mandate of the Presidency of the Republic of Ecuador regarding the obligation to use this type of package. The methodology was based on the analysis of the current reality of information technologies, studying both frontier scenarios in servers and network infrastructure; as well as the individual computers of each official of the institution